Association between presence in lectures and student knowledge gain in problem based learning: experience in Neuropsychiatry module, FMUI, International Program (Faculty of Medicine Universitas Indonesia, 2009)
Aim This study was conducted to determine the association between presence in lecture and examination scores. Methods This was a cross sectional study, conducted in the Faculty of Medicine University of Indonesia, International Class Program, from November 2007 to May 2008. The subject's inclusion criterion was FMUI International class students enrolled in the Neuropsychiatry module in 2007/2008. we excluded students who did not attend the examinations i.e. multiple choice questions (MCQ)-1, -2, or essay. The data collected were presence in lecture and examination scores. Data analysis was done using SPSS linear regression to see the association between presence in lectures and exam scores. Results The results showed that the R and P of the association between presence in lectures and exam scores were (R= 0.121, P= 0.413), (R= 0.212, P= 0.148), (R= 0.260, P= 0.075), and (R= 0.280, P= 0.054) for MCQ1, MCQ2, essay, and mean exam scores respectively. Conclusion We failed to show the association between presence in lectures and student knowledge gain. This result might be due to the many factors discussed that were not analyzed in this study. (Med J Indones 2008; 18: 131-4) Key words: exam, MCQ, essay